Factors affecting movement of prices in Malaysia's stock exchange: comparison between KLCI and Hijrah Shariah Index / Muhammad Asyraf Abdul Rahman - Abdul Rahman, Muhammad Asyraf (Faculty of Business Management, 2018)
Nowadays, excess fund is better being invested rather than keep in saving account. Through investing, excess fund can be multiplied. Stock exchange is where the best place to securely invest the excess fund available without the existence of fraudulent and scam. Along with growing of Islamic Finance, Shariah index has been introduced by Bursa Malaysia in the stock exchange on 21 st May 2007. With the existence of Shariah index, broad benchmark for Shariah-compliant investment has been provided. The general criteria is that, Shariah-compliant companies must not involve with activities deemed non permissible according to Shariah. The performances of stock exchange also represent the performances of economic activity in the country. However, the movement of prices in the stock exchange can be influenced by factors such as fundamental factors and psychological factors. Thus, The aim of this study is to examine how the prices movement of stock exchange is affected by fundamental factors. Fundamental factors that will be focused on upon this study are macroeconomic factors; namely gross domestic products, money supply, inflation rate and interest rate, and the crude oil (WTI) prices. The data being undergo several tests namely unit root test, correlation analysis, multicollinearity analysis, regression analysis, normality test, serial correlation test, varience analysis and functional form analysis. The tests are being done separately in between KLCI and Hijrah Shariah Index. Towards KLCI, it is found that inflation rate and crude oil prices shows significant relationship while gross domestic products, money supply and interest rate show insignificant relationship. Towards Hijrah Shariah Index, gross domestic products, inflation rate and crude oil prices show significant relationship while money supply and interest rate show insignificant relationship.